PROFILE OF VICTIMS OF SEXUAL VIOLENCE CASES AGAINST WOMEN EXAMINED AT THE HOSPITAL. Dr.PIRNGADI MEDAN PERIOD JANUARY 2021 TO JUNE 2023 - Sidauruk, Horas Ahmad; Sitepu, Agustinus; Marbun, Doaris Ingrid; Petrus, Asan; Lubis, Adriansyah (Fakultas Kedokteran Universitas Jenderal Soedirman, 2024)
Background: Forms of violence against women include physical, sexual, economic, political, and psychological violence that can be carried out by individuals, communities, and the state. The types of sexual violence that can occur are crimes, sexual violence (sexual violance) and obscenity. The purpose of this study is